Dying with behavioral and psychological symptoms of dementia in Australian nursing homes: a retrospective case-control study - Roach, Peter; Lovell, Melanie R.; Macfarlane, Stephen (Frontiers in Psychiatry, 2023)
Objectives: To identify predictors of mortality in people with active and challenging behavioral and psychological symptoms of dementia (BPSD). Design: A retrospective case-control study was designed to compare those referred to Dementia Support Australia (DSA) who died in the twelve months to November 2016, with an equal number of controls who did not die. An audit tool was designed after literature review and expert opinion from the service. Odds ratio calculations and the Mann-Whitney U test were used to assess for difference. Setting: Residents of Australian residential aged care facilities with BPSD referred to the DSA service. Participants: Of 476 patients referred to DSA during the study period, 44 died. 44 controls were randomly selected from those remaining matched for age and sex. Results: Significant differences included higher rates of benzodiazepine use, drowsiness, delirium, reduced oral intake and discussions about goals of care in those who died. Those who died were referred to the service for a shorter period and had more frequent contact between DSA and nurses at the nursing homes. Increase in opioid use and loss of skin integrity in those who died approached significance. The overall end of life course demonstrated a complex set of needs with frequent delirium, pain and frailty. Conclusions: Further study is required to determine the optimal care for those with BPSD at the end of their lives. This study would indicate complex end of life care needs and point to a role for palliative care support.